The Effect Of Electrical Installation Trainer Media On Undergraduate Students Learning Outcomes Of Domestic Electrical Installation Practice Course - Wendra Sufrianto; Oriza Candra (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of using an electrical installation trainer media on the learning outcomes of students practicing domestic electrical installations in the electrical engineering department of the State University Of Padang. This type of research is quantitative research. The research method used is an experimental research method with a True experimental design with a Posttest-Only Control Group Design type of research design. Collecting data using a research instrument that was given a post test in the form of multiple choice questions using random sampling, by dividing the sample into two, namely some undergraduate students as the experimental class and some undergraduate students as the control class by giving the same questions to all samples of undergraduate students in the class. domestic electrical installation practice. The hypothesis is carried out using T-test analysis, the T-test was used to analyze differences in undergraduate students learning outcomes using the electrical installation trainer media and other undergraduate students without using the electrical installation trainer media. The results showed that the use of the electrical installation trainer media had a significant effect on the learning outcomes of undergraduate students and indicated that there was a significant difference between the post test results of the experimental class using the electrical installation trainer media and the control class that did not use the electrical installation trainer.This study aims to analyze the effect of using an electrical installation trainer media on the learning outcomes of students practicing domestic electrical installations in the electrical engineering department of the State University Of Padang. This type of research is quantitative research. The research method used is an experimental research method with a True experimental design with a Posttest-Only Control Group Design type of research design. Collecting data using a research instrument that was given a post test in the form of multiple choice questions using random sampling, by dividing the sample into two, namely some undergraduate students as the experimental class and some undergraduate students as the control class by giving the same questions to all samples of undergraduate students in the class. domestic electrical installation practice. The hypothesis is carried out using T-test analysis, the T-test was used to analyze differences in undergraduate students learning outcomes using the electrical installation trainer media and other undergraduate students without using the electrical installation trainer media. The results showed that the use of the electrical installation trainer media had a significant effect on the learning outcomes of undergraduate students and indicated that there was a significant difference between the post test results of the experimental class using the electrical installation trainer media and the control class that did not use the electrical installation trainer.